PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI 2D BERBASIS MOTION GRAPHIC PADA MATERI SIMBOL PANCASILA UNTUK SISWA KELAS IV SEKOLAH DASAR - Aditya Imam Mahdi; Ina Sholihah Widiawati; Indrawan Ady Saputro (Jurnal Riset Multidisiplin Edukasi, 2026)
The low understanding of elementary school students regarding Pancasila symbol material is caused by the dominance of lecture-based teaching methods that are less effective in maintaining student focus and learning interest. This study aims to develop a learning medium in the form of a 2D animated video based on motion graphic techniques covering the introductory material of Pancasila symbols for fourth-grade students at SD Muhammadiyah PK Simo. The study employed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model with a mixed-methods approach combining qualitative and quantitative data. SWOT analysis was applied in the initial stage to systematically identify the needs for media development. Data were collected through observation, interviews, literature review, questionnaires, pretests, and posttests involving 20 fourth-grade students. Questionnaire data were analyzed using a four-point Likert scale, while learning improvement was measured using Normalized Gain (N-Gain). This study produced a 2D animated video using motion graphic techniques with a duration of 5 minutes and 28 seconds, developed using Adobe After Effect and Adobe Illustrator. Validation by educational practitioners showed an average score of 3.6, categorized as highly valid. The questionnaire results from 20 students yielded an average score of 3.53, also categorized as highly valid. N-Gain calculation results showed an average of 0.78, classified in the high category. The novelty of this research lies in the application of Adobe After Effect-based motion graphic techniques for Pancasila symbol learning in elementary schools, combined with the ADDIE model and SWOT analysis as a development framework. This medium is expected to serve as an innovative alternative in supporting the implementation of the student-centered Merdeka Curriculum.